Curriculum Management at STAI Yayasan Tarbiyah Islamiyah (YASTIS) Padang - Mutathahirin, Mutathahirin; Zainal, Dini Fitri; Wahyudi, Eri; Saputra, Ilham; Chantika, Melan; Yansah, Randa; Ramadani, Suci; Rahmi, Azvi; Helena, Helena; Zeky, Serpuadi; Monia, Fenny Ayu (Khalaqa: Journal of Education and Learning, 2025)
Curriculum development can be understood as a process that involves the selection, organization, implementation, and evaluation of learning experiences. This process is based on the needs, abilities, interests of students, and the demands of the community. Furthermore, curriculum development is a dynamic process that takes place continuously in line with existing developments. This allows it to be adapted to the current educational context while also providing the flexibility to adapt the curriculum over time. This research in general aims to research and improve the curriculum in higher education, especially in Stai Yastis Padang. This research uses a type of qualitative research with a library approach (Library Research) or known as literature study. The curriculum includes a set of knowledge or subjects that students must learn to achieve their educational goals.